Korean nursery rhymes : Wild geese, Land of goblins and other favorite songs and rhymes - Wright, Danielle. (Tuttle Pub. ; Distributed by North American, Latin America & Europe, 2013)
An illustrated collection of fourteen nursery rhymes, plus notes on Korean culture and explanations of how the jump rope and hand clap games are played. Presented in Hanguel script, Romanized Korean, and English; accompanying CD contains recordings of all of the rhymes performed in Korean and English.